Citicoline Treatment in Acute Ischemic Stroke: A Randomized, Single-Blind TMS Study - Premi, Enrico; Cantoni, Valentina; Benussi, Alberto; Gilberti, Nicola; Vergani, Veronica; Delrio, Ilenia; Gamba, Massimo; Spezi, Raffaella; Costa, Angelo; Padovani, Alessandro; Borroni, Barbara; Magoni, Mauro (Frontiers in Neurology, 2022)
Background: Although stroke imposes an enormous economic burden, treatment is far from satisfactory. Recent research suggests that drugs with the potential to enhance endogenous brain plasticity could reduce acute brain damage and improve functional recovery in animal models of stroke. One of these new drugs, which might combine neurovascular protection and repair effects, is Citicoline. Objectives: The objective of this randomized, single-blind experimental study was to evaluate whether the treatment with Rischiaril® Forte was able to restore intracortical excitability measures, evaluated through transcranial magnetic stimulation (TMS) protocols, in patients with acute ischemic stroke. Methods: Patients with acute ischemic stroke were recruited and assigned to eight-weeks therapy of standard treatment (control group - CG) or CDP-choline (Rischiaril® Forte 2000 mg) added to conventional treatment (treatment group - TG). Each subject underwent a clinical evaluation and neurophysiological assessment using TMS, pre- and post-treatment. Results: Thirty participants (mean [SD] age, 68.1 [9.6] years; 11 women [37%]) completed the study. We did not observe significant changes in clinical scores after CDP-choline treatment (all p>0.050), but we observed a significant improvement in short-interval intracortical inhibition (SAI) (p=0.003), in the TG compared to the CG group. Conclusions: Eight-weeks treatment with citicoline after acute ischemic stroke may restore intracortical excitability measures which partially depend on cholinergic transmission. This study extends current knowledge of the application of citicoline in acute ischemic stroke and expands knowledge.